Structural Integrity of Additive Manufactured Materials and Parts 2020
DOI: 10.1520/stp163120190128
|View full text |Cite
|
Sign up to set email alerts
|

On the Challenges toward Realization of Functionally Graded Structures by Electron Beam Melting—Fe-Base Shape Memory Alloy and Stainless Steel

Abstract: In the present study, an iron-manganese-aluminum-nickel (Fe-Mn-Al-Ni) shape memory alloy was processed on an austenitic steel (AISI 304) build platform by electron beam melting in order to study the feasibility of realizing functionally graded structures consisting of two different materials (i.e., a functional and a structural material). Compression specimens consisting of the processed shape memory alloy and the austenitic build platform in equal parts were investigated. The microstructure was analyzed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Numerous studies focused on AM of Ni-Ti revealed that the processing window of Ni-Ti seems to be rather small [27]. Recently, some of the current authors investigated AM of Fe-Mn-Al-Ni by L-PBF [28] as well as E-PBF [29]. It was shown that the alloy is generally suitable for processing by both AM techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies focused on AM of Ni-Ti revealed that the processing window of Ni-Ti seems to be rather small [27]. Recently, some of the current authors investigated AM of Fe-Mn-Al-Ni by L-PBF [28] as well as E-PBF [29]. It was shown that the alloy is generally suitable for processing by both AM techniques.…”
Section: Introductionmentioning
confidence: 99%